Assessment of knowledge and behavior regarding cardiovascular diseases and their risk factors among medical students of a private medical college in Lahore - Choudhry, Muhammad Ashraf; Ali, Hafiza Asma Riasat; Amin, Bushra; Ahsan, Tahira; Abbas, Nadir; Khan, Mujadad Ahmad (Journal of Fatima Jinnah Medical University, 2022)
Background: Cardiovascular diseases (CVD) are a major cause of premature deaths globally. The gap between knowledge and behavior regarding modifiable risk factors related to these diseases has been noticed in medical students and is associated with a high number of morbidity and mortality. The aim of this study was to assess knowledge and behavior regarding cardiovascular diseases risk factors among newly enrolled MBBS students. Subjects and methods: This cross-sectional study was conducted from May to September 2021. A total of 140 first-year MBBS students participated including 80 females and 60 males. Data were collected through a self-administered questionnaire having 17 questions and two sections, one for knowledge assessment and the other for the behavior of participants regarding CVD risk factors. Results: Major risk factors for heart disease identified by students included obesity (99.3%), high cholesterol (98.6%), hypertension (97.9%), lack of physical activity (95.7%), smoking (82.1%), older age (89.3%), family history of heart disease (73.6%) and diabetes (78.6%). Pertaining to personal history, 10% were smokers, 32.1% regularly consumed soft drinks and 79.3% reported having any physical activities. Significant differences were found between male and female students regarding knowledge of CVD risk factors such as smoking (p-value = 0.003). Similarly, significant differences were observed between male and female students heart health behavior such as cholesterol checkup (31.7% vs. 16.2%, p-value = 0.032), use of soft drinks (48.3% vs 20%, p-value = 0.001) and physical activity (90% vs. 71.2%, p-value = 0.007). Conclusion: First-year medical students have good knowledge of CVD risk factors but the behavior, regarding practice to avoid these risk factors, needs improvement. It was also observed by comparison that male students have more knowledge of heart disease risk factors as compared to female students.